Quantitative source apportionment of heavy metals in atmospheric deposition of a typical heavily polluted city in Northern China: Comparison of PMF and UNMIX - Cai, Angzu; Zhang, Haixia; Zhao, Yawei; Wang, Xiaojian; Wang, Litao; Zhao, Hui (Frontiers in Environmental Science, 2022)
Receptor models are rarely utilized in atmospheric deposition but are often used to identify pollutant sources and quantify their contribution. This paper focuses on the soil in atmospheric deposition in typical polluted city. Atmospheric deposition has become an important route for exogenous heavy metals input ecosystems. In this study, the heavy metals in atmospheric deposition were determined in three monitoring points arranged in Handan City. According to the functional area, fluxes, sources and accumulation in soil were explored. The sources of heavy metals were identified by PMF (positive matrix factorization) and UNMIX. The accumulation of heavy metals in soil was predicted. The results showed that the deposition fluxes in industrial area were higher than other functional area. The mean concentrations of 8 heavy metals (Cd, Cr, Cu, Mn, Ni, Pb, Zn, As) in the atmospheric deposition exceed their background values. PMF identified 5 major sources and UNMIX analyzed 4 sources. Similar source apportionment results were acquired via PMF and UNMIX, which were combustion of fossil fuels, steel smelting emission, road dust and industrial source. Steel smelter emission was the highest source contributor. Therefore, combining these two models was the most effective approach, and more attention should be paid to mitigating the pollution caused by the industrial activities. The prediction indicated that the accumulation of heavy metals from atmospheric deposition to soil would increase in 30 years, the growth rate of Cd increased significantly. The results of this study could provide reference in reduction of heavy metal pollution in atmospheric deposition.